Kedudukan Anak Perempuan Sebagai Sentana Rajeg Menurut Hukum Adat di Desa Adat Kuta Kabupaten Badung - Ni Wayan Setiari; I Nyoman Budiartha; Diah Gayatri Sudibya (Jurnal Interpretasi Hukum, 2021)
Nyentana is a form of marriage based on changes in the status of purusa from the daughter's side and from the male's status as pradana. This study aims to examine the implementation of nyentana rajeg marriages in the Traditional Village of Kuta, Badung Regency and analyze the position of the heirs of daughters in rajeg marriages in the Traditional Village of Kuta, Badung Regency. The type of research used is empirical legal research with a statutory approach. Sources of data used are primary and secondary legal materials collected through interview techniques and literature study. After the data is collected, it is then processed and analyzed descriptively. The results showed that the implementation of sentana rajeg marriage in the Traditional Village of Kuta, Badung Regency, namely women whose status was changed to men (purusa) based on their inner and outer bond and love for each other. It is stated in Awig-awig in Kuta Traditional Village, Nyentana marriage, in which the woman proposes to the man to be brought to the woman's residence and the final ceremony is held at the man's house and witnessed by the soldiers of the two villages. The position of the heirs of daughters in sentana rajeg marriages in the Traditional Village of Kuta, Badung Regency, namely Purusa in Hinduism is interpreted as a male or female descendant of Putrika who is suputra who will carry out and continue his Swadarma as a descendant of Kapurusa. After the daughter is married, her status is changed to Sentana Rajeg, who will become the heir, has rights and responsibilities towards parents, merajan, and inheritance